2020
DOI: 10.1096/fj.201902254rr
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone‐induced microRNAs act as feedback regulators of mineralocorticoid receptor signaling in kidney epithelia

Abstract: The final steps in the Renin‐Angiotensin‐Aldosterone signaling System (RAAS) involve binding of the corticosteroid hormone, aldosterone to its mineralocorticoid receptor (MR). The bound MR interacts with response elements to induce or repress the transcription of aldosterone‐regulated genes. A well characterized aldosterone‐induced gene is the serum and glucocorticoid‐induced kinase (SGK1), which acts downstream to increase sodium transport in distal kidney nephron epithelial cells. The role of microRNAs (miRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 82 publications
(159 reference statements)
0
8
0
Order By: Relevance
“…For example, the miR-466 family, consisting of mir-466a, miR-466b, miR-466c, and miR-466e, not only negatively regulates the expression of the MR, but also the expression of one of its well-known target genes, SGK1. It could be shown that the expression of the miR-466 family is induced by aldosterone in the collecting duct, suggesting a negative feedback loop [ 171 ]. While some of the miRs seem to be part of negative feedback loops in MR regulation, there is also evidence that, under pathologic conditions, the expression of MR regulating miRs decreases.…”
Section: Mr Signaling and Micromilieumentioning
confidence: 99%
“…For example, the miR-466 family, consisting of mir-466a, miR-466b, miR-466c, and miR-466e, not only negatively regulates the expression of the MR, but also the expression of one of its well-known target genes, SGK1. It could be shown that the expression of the miR-466 family is induced by aldosterone in the collecting duct, suggesting a negative feedback loop [ 171 ]. While some of the miRs seem to be part of negative feedback loops in MR regulation, there is also evidence that, under pathologic conditions, the expression of MR regulating miRs decreases.…”
Section: Mr Signaling and Micromilieumentioning
confidence: 99%
“…RAAS is essential for the management of renal salt, water conservation, and blood pressure [ 32 ]. Importantly, changes in miRNAs expression have been shown to have an influence on the components of the RAAS pathway [ 33 ]. miR-466a/b/c/e family has been shown to be regulated by aldosterone (ALDO) and contributes to a negative feedback loop that reduces long-term ALDO signaling.…”
Section: Mirnas In Kidney Physiology and Diseasementioning
confidence: 99%
“…miR-466a/b/c/e family has been shown to be regulated by aldosterone (ALDO) and contributes to a negative feedback loop that reduces long-term ALDO signaling. Thus, the miR-466a/b/c/e family protects aldosterone-sensitive tissues from excessive ALDO exposure [ 33 ] and plays an important role in kidney homeostasis. Furthermore, miR-6869-5p has also been described as a regulator of the RAAS cascade [ 34 ].…”
Section: Mirnas In Kidney Physiology and Diseasementioning
confidence: 99%
“…On the opposite, MR transcript levels increase under hypotonicity thanks to the recruitment of Human antigen R (HuR), another RBP, which interacts with MR 3′-UTR in the cytoplasm of renal cells to stabilize and increase MR levels, thereby modulating MR signaling [ 24 ]. Accumulating evidence now underscores the pivotal role of microRNAs (miRNAs), an additional class of post-transcriptional regulators, in the control of MR expression in the kidney [ 25 , 26 ]. Beyond these regulatory mechanisms, MR activity and signaling are also modulated by post-translational modifications such as ubiquitylation, SUMOylation, phosphorylation, and acetylation [ 13 , 27 ].…”
Section: Mineralocorticoid Signaling Pathwaymentioning
confidence: 99%